Percutaneous cryoablation for the treatment of medically inoperable stage I non-small cell lung cancer. - Yoshikane Yamauchi (Public Library of Science (PLoS), 2012)
Background To evaluate the midterm results of percutaneous cryoablation for medically inoperable stage I non-small cell lung cancer. Methodology/principal findings Between January 2004 and June 2010, 160 patients underwent computer tomography guided percutaneous cryoablation for lung tumors at our institution. Of these patients, histologically proven stage I lung cancer patients with more than one year of follow-up, were retrospectively reviewed. All of these patients were considered to be medically inoperable with Charlson comorbidity index of 3 or greater. Follow-up was based primarily on computed tomography. There were 22 patients with 34 tumors who underwent 25 sessions of cryoablation treatment. Complications were pneumothoraces in 7 treatments (28%, chest tube required in one treatment), and pleural effusions in 8 treatments (31%). The observation period ranged from 12-68 months, average 29±19 months, median 23 months. Local tumor progression was observed in one tumor (3%). Mean local tumor progression-free interval was 69±2 months. One patient died of lung cancer progression at 68 months. Two patients died of acute exacerbations of idiopathic pulmonary fibrosis which were not considered to be directly associated with cryoablation, at 12 and 18 months, respectively. The overall 2- and 3-year survivals were 88% and 88%, respectively. Mean overall survival was 62±4 months. Median overall survival was 68 months. The disease-free 2- and 3-year survivals were 78% and 67%, respectively. Mean disease-free survival was 46±6 months. Pulmonary function tests were done in 16 patients (18 treatments) before and after cryoablation. Percentage of predicted vital capacity, and percentage of predicted forced expiratory volume in 1 second, did not differ significantly before and after cryoablation (93±23 versus 90±21, and 70±11 versus 70±12, respectively). Conclusions/significance Although further accumulation of data is necessary regarding efficacy, cryoablation may be a feasible option in medically inoperable stage I lung cancer patients.